Prevalence of Hepatitis B and C in District Dir Upper, Khyber Pakhtunkhwa, Pakistan - Shahzeb Khan Shaz; Noor Ullah; Iqra Rafi que (Global Journal of Clinical Virology - Peertechz Publications, 2019)
The current study was performed on the dominance of hepatitis B and C in three tehsils of District Dir upper namely Dir, Wari and Sheringal. The data were collected from three tehsils in which 11 were positive cases and 339 were found negative cases during my research work.